Integrative approach for validation of six important fish species inhabiting River Poonch of north-west Himalayan region (India) - Awas, Mohd; Ahmed, Imtiaz; Ahmad, Syed Mudasir; Al-Anazi, Khalid Mashay; Farah, Mohammad Abul; Bhat, Basharat (Frontiers in Genetics, 2023)
Traditionally, species of fish are identified based on morphological characteristics. Although these taxonomic descriptions are essential, there are cases where the morphological characters distinguishing these species show marginal differences. For instance, in the Poonch River in the Himalayas, there are 21 species, out of which some are morphologically similar, and the taxonomic distinction between these species is unclear. Therefore, in this study, we used sequences from two mitochondrial genes, Cytochrome b (Cyt b) and a larger ribosomal subunit (16S rRNA), as well as the morphological analysis to address any taxonomic ambiguities among the six fish species. Maximum Likelihood results revealed that all the species were clustered according to their families and genera. The phenotypic analysis also supported this statement, as all the species of different genera like Schizothorax, Tor, Garra, Traqilabeo, and Glyptothorax are grouped in their particular cluster, it shows that species of a separate class share a mutual morphological characteristic. While genetic analyses of these species suggest nucleotide diversity (p) and haplotype diversity, with Hd values as 0.644 for Cyt b and 0.899 for 16S rRNA, confirming the rich genetic diversity in the river. Overall, we recommend that the integrative approach in delimiting the fish species is more effective than the individual one and can be used to rapidly diagnose a species and understand the evolutionary relationship between the species.